Pengoptimalan Pelaksanaan Pembangunan Desa Motihelumo Kabupaten Gorontalo Utara melalui Pendampingan Perumusan dan Pengintegrasian Sustainable Development Goals dalam Perencanaan Desa - Hartono Mamu; Regina Valentine Aydalina (Univeristas Negeri Gorontalo, 2022)
The success of “Developing Villages” is very much determined by a careful planning that is able to answer problems and anticipate opportunities and challenges that arise carefully and in the process carried out in a participatory manner by involving all stakeholders including the community and village officials/apparatus.The method used in the implementation of the Thematic Village Community Service Program is mentoring. At the end of this activity, a village planning document was obtained in the form of a Village Program Work Plan (RKPD).